The Value of Character Education in Denias Senandung Film Above the Clouds and Its Relevance for MI-Age Children: Nilai Pendidikan Karakter Dalam Film Denias Senandung Diatas Awan dan Relevansinya Bagi Anak Usia MI - Ziyadatur Rohmah Mizan; Nur Maslikhatun Nisak Nisak (Academia Open, 2022)
This research method uses content analysis method. In this method, the researcher uses it with the aim of re-explaining the value of character education in the film Denias Senandung di Atas Awan. In accordance with the research that has been done, conclusions are obtained. First, the film Denias Senandung above the Clouds has at least 11 characters that can be imitated. Religious, disciplined, hard working, honest, independent, curious, friendly/communicative, appreciative of achievement, peace-loving, socially caring, and responsible. Second, the relevance of the value of character education in the film Denias Senanadung di Atas Awan will be very good if it is taught and applied to MI-age children in their daily activities. Due to the many teachings, wisdom, messages as well as important lessons that are able to educate in this film. Judging from its development, MI-age children will very quickly imitate what they see, so watching the film Denias Senanadung di Atas Awan in the hope that it will instill positive lessons in children. Highlights: Content analysis reveals 11 imitable character traits in the film Denias Senandung di Atas Awan: religious, disciplined, hardworking, honest, independent, curious, friendly/communicative, appreciative of achievement, peace-loving, socially caring, and responsible. The value of character education in the film is highly relevant for MI-age children, as it offers numerous teachings, wisdom, messages, and important lessons that can be applied to their daily activities. Watching Denias Senandung di Atas Awan can quickly influence MI-age children to imitate positive behaviors, making it a valuable tool for instilling positive lessons and values in them Keywords: content analysis, character education, Denias Senandung di Atas Awan, film, MI-age children.